Max–min fairness beamforming design for UAV‐enabled integrated sensing and communication - Li, Peng; An, Chunlian; Lei, Mingdong (Electronics letters, 2024)
This paper investigates the design of transmit beamforming in an integrated sensing and communication system, where an unmanned aerial vehicle (UAV) equipped with a uniform linear array (ULA) transmits combined information‐carrying and dedicated sensing signals to perform multi‐user communication and simultaneously sense potential targets. First, the transmit beamforming design is formulated as a series of non‐convex optimisation problems, and then jointly design the information and sensing beamforming to maximise the minimum communication rate under an optimised UAV deployment location, subject to the sensing beampattern gain requirements and the limited transmit power of the UAV. However, due to the application of ULA on the UAV, the formulated problems are highly non‐convex and difficult to solve optimally. To address the aforementioned issue, an efficient algorithm is proposed to find suboptimal yet high‐quality solutions. This is achieved by adopting the successive convex approximation and semidefinite relaxation. The numerical results confirm the effectiveness of the proposed algorithm and demonstrate that the transmit beamforming design achieves a balance between communication and sensing performance. This paper studies the design of transmit beamforming in an integrated sensing and communication system, where an unmanned aerial vehicle equipped with a uniform linear array transmits combined information‐carrying and dedicated sensing signals to perform multi‐user downlink communication and simultaneously sense potential targets.